1970
DOI: 10.1029/wr006i004p01154
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Relations in Properties of Unconsolidated Quartz Sands and Silts Pertaining to Water Flow

Abstract: During a laboratory investigation using radiotracers, empirical formulas were developed to replace the ambiguous or incorrect Dupuit‐Forchheimer assumption used in relationships governing the flow of water through porous, unconsolidated materials ranging from clay to coarse sands or fine gravels. The Dupuit‐Forchheimer assumption states that the ratio of specific flow rate to average flow velocity is equal to porosity, but it is not specified whether true porosity or void ratio or specific yield, also called e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…properties of coastal sands have reported their results in terms of permeability, estimation of K s from published data on permeability revealed that observed K s values were comparable to those reported for coastal sands (Wiebenga et al (1970); Wilson et al, 2008). One similarity between coastal sands subjected to wave action or currents, and mechanically separated bauxite residue sand is the high degree of sorting and poor consolidation that results in a high total porosity and hydraulic conductivity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…properties of coastal sands have reported their results in terms of permeability, estimation of K s from published data on permeability revealed that observed K s values were comparable to those reported for coastal sands (Wiebenga et al (1970); Wilson et al, 2008). One similarity between coastal sands subjected to wave action or currents, and mechanically separated bauxite residue sand is the high degree of sorting and poor consolidation that results in a high total porosity and hydraulic conductivity.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, for wellsorted coastal sediments dominated by fine and coarse quartz sand, K s values of 17 to 2592 m day − 1 , and total porosities of 38 to 44% have been reported in literature (e.g. Wiebenga et al, 1970). Similarly, 23 separate studies conducted on well-sorted marine sands reported K s values of 2 to 353 m day − 1 (Wilson et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Wiebenga et al . [] tested 13 samples of quartz sands and silts from Australia. Cabalar and Akbulut [] measured hydraulic conductivity values of 16 Narli sands and 16 crushed stone sands from Turkey.…”
Section: Comparison With Equations In the Literaturementioning
confidence: 99%
“…The porosity property is not available in the test results of Alyamani and Sen [] thus only the experiments of Wiebenga et al . [] and Cabalar and Akbulut [] are compared. It can be seen that the Kozeny‐Carman model underestimates most of the results.…”
Section: Comparison With Equations In the Literaturementioning
confidence: 99%